2023
DOI: 10.1192/j.eurpsy.2023.1413
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking behaviour among healthcare workers with COVID-19

Abstract: IntroductionThe COVID-19 pandemic had a considerable psychosocial impact on healthcare workers (HCWs) who were constantly requested during this era with an increased risk of infection. This implies behavioural changes, especially in smoking behaviour.ObjectivesTo study smoking behaviour in HCWs with COVID-19.MethodsA cross-sectional descriptive study conducted in the department of occupational pathology of Charles Nicolle Hospital in Tunis involving the smoking HCWs affected by COVID-19 during the period from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study conducted with primary HCWs found that high level distress was associated with smoking (Abdu et al, 2023). It has been shown that the number of daily cigarettes smoked is higher in HCWs with burnout and who are exposed to a high physical and mental load during COVID-19 (Al-Otaibi et al, 2023;Ziedi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with primary HCWs found that high level distress was associated with smoking (Abdu et al, 2023). It has been shown that the number of daily cigarettes smoked is higher in HCWs with burnout and who are exposed to a high physical and mental load during COVID-19 (Al-Otaibi et al, 2023;Ziedi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%